Utilization Of Traditional And Medical Treatment During The Covid-19 Pandemic - Izza Azzahra; Ramayani Anwar; Sarah Mumtaz; Yohana Ingrid Lorenza (International Archives of Medical Sciences and Public Health, 2021)
People experience fear in taking treatment during the COVID-19 pandemic, especially treatment at health facilities. Traditional medicine is an alternative for people when they have health problems. This study aims to determine the use of health and traditional medicine. This research uses cross-sectional design data analysis (study of the cross-sectional survey) and primary data collection using Google form. The results of this study indicate that the number of respondents who used traditional medicine in the last three months was 388 people (46.8), not at all using traditional medicine as many as 280 people (33.8%), the most frequently visited health facilities are Telemedicine, with a total of 609 people. The public health centre is a health facility that ranks second most visited with 273 people. In a pandemic situation like this, the number of people who have experienced illness in the last 30 days is 465 respondents, where headaches have the highest number suffered in the last 30 days. The North Sumatra Provincial Health Office must innovate in medical treatment by paying attention to traditional medicine. The North Sumatra Provincial Health Office must improve the quality of medical services in overcoming health problems.